Understanding the Summary Jurisdiction in NSW - Mitchell, Tanya Louise (2017)
This thesis presents an analysis of the NSW summary criminal jurisdiction (the ‘summary jurisdiction’). The summary jurisdiction is a dynamic criminal justice apparatus where magistrates preside over the determination of liability for certain proscribed behaviours in the lower courts without the intervention of a jury. My close analysis of the summary jurisdiction tells the previously little-known story of its development and offers a basis for critique. Adopting a socio-historical approach, this thesis offers a fresh analysis. At a broad level, change over time in the summary jurisdiction can be seen as following a trajectory of formalisation. I argue that ‘formalisation’ is a useful concept for understanding the historical development of the summary jurisdiction. It has four overlapping and interacting dimensions that assume differing degrees of significance at different times. Those dimensions are: juridification; rationalisation; professionalisation together with what I call ‘lawyerification’; and the separation of law from other spheres of social power. Formalisation has been a product of changing legitimation demands and attempts to increase the efficiency of the criminal law. Applying formalisation as a lens through which to view the development of the summary jurisdiction reveals how the summary jurisdiction has achieved the criminalisation of behaviours that have been constructed as harmful